Postmortem investigations on leatherback sea turtles (Dermochelys coriacea) stranded in the Canary Islands (Spain) (1998–2017): Evidence of anthropogenic impacts. (June 2021) - Orós, Jorge; Camacho, María; Calabuig, Pascual; Rial-Berriel, Cristian; Montesdeoca, Natalia; Déniz, Soraya; Luzardo, Octavio P.
Abstract: Opportunities for postmortem studies on leatherback sea turtles ( Dermochelys coriacea ) are infrequent due to their predominantly pelagic life history. In this study, the pathological findings and causes of mortality of 13 leatherback turtles stranded in the Canary Islands, Spain, from 1998 to 2017, are described. In addition, concentrations of Se, As, Cd, Pb, Hg, 15 rare earth elements (REE) and other 4 minor elements (ME), 41 persistent organic pollutants, and 16 polycyclic aromatic hydrocarbons in hepatic samples from 5 leatherbacks were determined. 84.62% of the turtles died possibly due to anthropogenic causes (entanglement/fishing interaction - 46.15%; boat strike - 23.07%; plastic ingestion - 15.38%). Although Se, As, and Cd were found at higher hepatic concentrations than those reported for leatherbacks from other locations, no acute lesions were detected. This is the first report of exposure to REE-ME in sea turtles. Organic contaminant hepatic concentrations were generally low or undetectable. Graphical abstract: Unlabelled Image Highlights: The majority of leatherback turtles in this study died due to anthropogenic causes. We detected high hepatic levels of Se, As, and Cd in absence of acute lesions. This is the first report of exposure to rare earth elements in leatherbacks. Ileocecal diverticulitis can lead to fatal septicemia in leatherbacks.